MORFOFONEMIK BAHASA JAWA DIALEK BANYUMAS - Yani Paryono (Widyariset, 2010)
The study of Morphophonemic on Javanese of Banyumas Dialect is part of phonology and morphology. Morphophonemic process is the change processes of morphemic form in the process of morphologic, either affixation, clitich, composition, reduplication or internal modification. To answer the problems in this study, the writer uses the structural theory and qualitative descriptive approach. The result of the study shows that morphophonemic process in Javanese of Banyumas Dialect occurred on affixation and internal modification cause the process of phonemic as the change of phoneme, phoneme appearance, phoneme omission, and phoneme perpetuation. One of four kinds of phonemic processes that mostly occured in morphophonemic process is affixation and internal modification process seldom occured.